BERAGAM CARA MENGENAL JURNALISTIK DALAM ISLAM: PERSPEKTIF AL-QUR’AN - Achmad Yaman (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
The purpose of this research is to understand Islamic journalism from the perspective of the verses of the Qur'an. This research only uses library research which is part of a qualitative approach. Data analysis by interpreting existing literature, for example books, journals, ulama books and websites that match the research theme. The conclusion of the study is that the significance of qalam is in its function as a medium. Meanwhile, the media is only an introduction to knowledge, while knowledge cannot be captured without going through the process of reading and interpreting by humans and it is described in it how the Al-Quran is described with Al-Qalam with the aim and purpose of ensuring that the divine message can reach the target audience. Al-Qur'an as a holy book can be categorized as a medium for providing journalistic information to its readers. As a provider of journalistic information, the Al-Qur'an has a source of information, a function as an educator, a critical function, a social monitoring function and has an influence on the development and development of an era.